The Effect of Training and Development on Employee Productivity in the Digital Age - Ertawan Juliadi; Muhammad Syafri; Nanda Hidayati (Westscience Press, 2023)
This research explores the impact of training and development initiatives on employee productivity in the digital age within start-up companies in Indonesia through a quantitative analysis. A diverse sample of 500 employees from various sectors provided valuable insights. The findings revealed a positive correlation between the effectiveness of training programs and employee productivity, emphasizing the unique dynamics of training in start-ups. The study also uncovered the moderating effect of employee engagement and the mediating role of the perceived work environment. These results contribute to the understanding of how strategic investments in training and development can foster a skilled and productive workforce in the dynamic landscape of Indonesian start-ups.